2008
DOI: 10.1016/j.jcrysgro.2007.09.045
|View full text |Cite
|
Sign up to set email alerts
|

GaN:-Mg grown by MOVPE: Structural properties and their effect on the electronic and optical behavior

Abstract: The effect of Mg δ-doping on the structural, electrical and optical properties of GaN grown via metalorganic vapor phase epitaxy has been studied using transmission electron microscopy, secondary ion mass spectroscopy, atomic force microscopy, x-ray diffraction, Hall effect measurements and photoluminescence. For an average Mg concentration above 2.14 × 10 19 cm −3 , phase segregation occurs, as indicated by the presence of Mg-rich pyramidal inversion domains in the layers. We show that δ-doping promotes, in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Based on the Gaussian fittings, the dominant BL emission lines of the uniformly-doped and delta-doped sample were 2.86 eV and 2.89 eV, respectively. The blue shift of BL band peak in delta-doped sample is ascribed to the increase of coulomb energy resulting from the reduction of average distance between the donor-acceptor pair in the thin Mg-delta-doped region [41]. It can also be observed that the Mg-delta-doped sample shows additional violet luminescence (VL) emission bands peaked at 3.41 eV and 3.27 eV.…”
Section: Experimental Details and Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on the Gaussian fittings, the dominant BL emission lines of the uniformly-doped and delta-doped sample were 2.86 eV and 2.89 eV, respectively. The blue shift of BL band peak in delta-doped sample is ascribed to the increase of coulomb energy resulting from the reduction of average distance between the donor-acceptor pair in the thin Mg-delta-doped region [41]. It can also be observed that the Mg-delta-doped sample shows additional violet luminescence (VL) emission bands peaked at 3.41 eV and 3.27 eV.…”
Section: Experimental Details and Resultsmentioning
confidence: 90%
“…4. The increment of Mg ions concentration in the thin Mg-delta-doped region decreases the Fermi level and raises the local conduction band [41]. The delta-doped region with higher potential may serve as an electron blocking layer.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…We started with 45 perovskite materials, combining 3 inorganic cations, 5 metals, and 3 halogens, as shown in figure 1. The geometry of the perovskites are optimised in all the 3 phases (cubic, orthorhombic, and tetragonal) using the PBE exchange-correlation functional [43] in order to get the structures with the lowest potential energy. The initial lattice parameters of the perovskites are given in supplementary information is available online at stacks.iop.org/MRX/7/055502/mmedia.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Inorganic materials are known to have higher stability than the organic materials, especially at higher temperatures [29][30][31]. This aspect has been exploited quite well experimentally, in which the organic cation has been replaced by the inorganic Cs + cation that resulted in a rapid decrease in instability problems, thereby promising a relatively higher intrinsic or thermodynamic stability against decomposition to binary halide products [32][33][34][35][36][37][38][39][40][41][42][43][44]. However, theoretical investigation towards this pressing issue is still limited [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Mg-delta-doped GaN claimed that this method not only effectively improve the material quality, but also increases the hole concentration by the reduction of Mg activation energy and self compensation effect. [4][5][6] In this way, a hole concentration near 10 18 cm À3 could be obtained. Nevertheless, few works have been published on the growth or properties of n-type Si-delta-doped GaN, 7,8 among which the mobility behavior has not yet been concerned about.…”
mentioning
confidence: 94%